The role of the United Nations in protecting the internally displaced persons in Syria (2011-2018) - Aesyah Talib (Abdul Hamid Abu Sulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research aims to study the effectiveness of the role played by the United Nations (UN) in protecting internally displaced persons (IDPs) in Syria during the civil war, focusing on the time period between 2011 until 2018. This research focused on the legal framework for the protection of IDPs, the operations done by the UN in Syria, the challenges they faced and how they coped with the challenges. Then, this research proceeded to evaluate the strengths and weaknesses of the role played by the UN in order to understand the effectiveness of the UN’s role. The data collection for this research were mainly done based on primary and secondary sources such as reports by the UN, the adopted UN resolutions and international law documents. In addition, the data collection was also done through interview sessions with Malaysian NGO officers who worked in Syria and Syrian refugees staying in Malaysia. Then, the data were analysed through thematic analysis. Three themes were chosen based on the working scope of the UN, namely the administration, humanitarian aid, and civil, political and socioeconomic rights. This study has established that the role of the UN in protecting the Syrian IDPs was ineffective. This research showed there were some weaknesses that greatly influenced the role of the UN and deterred its effectiveness.